2005
DOI: 10.1017/s1743921306009240
|View full text |Cite
|
Sign up to set email alerts
|

Science case for VLT-Planet Finder

Abstract: Abstract. This paper presents the scientific case for a next generation adaptive optics instrument at the VLT, temporarily named "Planet Finder", that is aimed at detecting and characterizing extrasolar planets through the direct analysis of their emitted photons in the visible and at near-IR wavelengths. We discuss the observational niche of such an instrument to have first light in 2010, in complement to other planet search methods. To improve the efficiency (and consistency) of the search for planets with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This main observing mode of IRDIS is based on the principle of differential imaging initially proposed by Racine, et al (1999) and recently demonstrated on the VLT NACO instrument with the SDI device Close, et al 2006).…”
Section: Instrument Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…This main observing mode of IRDIS is based on the principle of differential imaging initially proposed by Racine, et al (1999) and recently demonstrated on the VLT NACO instrument with the SDI device Close, et al 2006).…”
Section: Instrument Conceptmentioning
confidence: 99%
“…The science cases and potential targets of the VLT Planet Finder are discussed in greater details by Moutou, et al (2006) in these proceedings.…”
Section: Introductionmentioning
confidence: 99%